Childhood in a global perspective - Wells, Karen C. (Polity Press, 2009)
This compelling new book offers a unique global perspective on children's lives throughout the world. It shows how the notion of childhood is being radically re-shaped, in part as a consequence of globalization. Taking an engaging historical and comparative approach, the book discusses wide-ranging issues such as children and war, child labour and young people's activism around the globe.